Spinal cord infarction after chemoembolization of bilateral breast tumor: a case report.: Infarto de médula espinal después de quimioembolización de tumor de mama bilateral: un reporte de caso - Cervera Ocana, Wilton Luis (2021)
Spinal cord infarction is a rare entity that can be caused by interventional procedures such as chemoembolization, despite its high level of safety. We present a case of a 51-year-old female with chest pain and hemorrhage from a friable neoplastic lesion of the bilateral breast without improvement after conservative measures. After embolization of the tumor arteries, the patient developed crural paraparesis and global lower extremity hyporeflexia. MRI showed hypersignal in the anterior spinal cord, suggesting ischemia/infarction of the spinal cord in the territory of the anterior spinal artery. Despite the interventional procedures being safe, the inherent risks are always present, and unfortunately some serious ones, such as the one reported in this case. That is why the importance of case-by-case evaluation in order to offer the best treatment and maintain informed consent.